Xenophobia in urban spaces: Analyzing the drivers and social justice goals from the Ugandan-Asian debacle of 1972 and xenophobic attacks in South Africa (2008-2019) - Sempijja, Norman; Mongale, Collin Olebogeng (Frontiers in Sustainable Cities, 2022)
Xenophobic attacks have long been prevalent in post-independence Africa, as shown by the expulsion of Ugandans of Asian origin from Uganda in 1972. Post-apartheid South Africa has experienced continuous xenophobic attacks on Africans since 2008. In both cases the attacks were not framed as xenophobic by the state. Instead, they were framed within a socio-economic context, where the targeted groups were criminalised and securitised by the general population. Thus, it is the goal of this qualitative study is to analyse the drivers and social justice goals of xenophobia in urban spaces. This is done by looking into case studies of the 1972 Ugandan-Asian expulsion in Uganda, and the xenophobic attacks on foreigners in South Africa (2008 to 2019). The case studies provided key debates surrounding the drivers and social justice goals of xenophobic attacks in both Uganda and South Africa. The paper examines the relative deprivation in both countries, which assists in explaining the onset of the xenophobic attacks.